PENGARUH ROTASI AUDIT AKUNTAN PUBLIK DAN ANNUAL FEE KANTOR AKUNTAN PUBLIK TERHADAP KUALITAS AUDIT - , Eko Suprapto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study is aimed at examining the determinant factors for audit quality. Based on the literature review, the study hypothesized that audit partnerâs adherence on audit rotation regulation, audit firmâs annual fees, and initial balance testing have positive effect on audit quality. Additionally, this study also hypothesized that audit tenure or the length of audit partnerâs engagement has negative effect on audit quality. Different from the previous studies, this study use audit partnerâs adherence on professional audit standard as the proxy for actual audit quality. The empirical results show that across models, audit firmâs annual fees and initial balance testing are the two determinant factors which provide positive effect on audit quality. Other results show that, audit partnerâs adherence on audit rotation regulation and the length of audit partnerâs engagement do not provide effect on audit quality. The meaning of those results show that audit rotation restriction until maximum three years does not provide effect on audit quality.